Family planning in Primary Health Care, and nursing care (Research, Society and Development, 2020)
This study aims to describe which contraceptive methods are understood in the context of family planning, and to understand the nursing professional's assistance in Primary Health Care. This is a descriptive, qualitative, integrative literature review study , carried out by searching for articles indexed in the Virtual Health Library (VHL), with the help of the following databases: Scientific Electronic Library Online (SCIELO), National Center for Biotechnology Information (PUBMED), Latin American Literature and the Caribbean in Health Sciences (LILACS), Nursing Database (BDENF), and Electronic Journals in Psychology (PEPSIC). The inclusion criteria include literature review research available in the databases described, between the years 2010 to 2020. The exclusion criteria were duplicate, incomplete articles, abstracts, reviews, experience reports, articles published in annals of events and unavailable in full. To collect the data, 17 articles were analyzed. The results of the study show that the main methods of family planning offered in Primary Health Care are: pill, mini-pill, hormonal injectable, condom, tubal ligation and vasectomy. The nurse has the task of guiding the population as to the way of use, effectiveness, side effects, and implications for sexual life. We conclude that family planning is associated with health education as an instrument to prevent unwanted pregnancies, the nurse acts as a mediator between the service and the population, seeking better strategies to guarantee sexual and reproductive health rights.